PERBAIKAN POSTUR KERJA DENGAN MENGGUNAKAN METODE RULA DAN RWL UNTUK MEMINIMALKAN GANGGUAN MUSCULOSKELETAL DISORDERS DI PT. XYZ - Gumilang, Dicky; Ananto, Kurniawan Dwi (Teknik Industri Unikom, 2022)
ABSTRACT In the manufacturing industry some material handling tasks are carried out manually or manual material handling (MMH). Excessive use of muscles or muscles receiving static loads repeatedly for long periods of time, without being supported by a natural posture can cause injury to workers. Musculoskeletal disorders are injuries or disorders that can affect the movement of the human body or the musculoskeletal system, such as muscles, and ligaments. The high rate of injuries, occupational diseases, or work accidents due to MMH in addition to harming workers, will also have a negative impact on company performance, including a decrease in company productivity, high medical expenses, employee absenteeism and a decrease in work quality. To reduce the risk of work accidents due to manual handling errors that cause musculoskeletal disorders (MSDs), an assessment of work posture is carried out using the Rapid Upper Limb Assessment (RULA) and Recommended Weight Limit (RWL) methods. The purpose of this study is to assess the work posture of employees in the production division of PT. XYZ and to make improvements to the work postures that are considered harmful to the ergonomics of the human body so as to minimize musculoskeletal disorders (MSDs) in workers. Key words: Manual Material Handling, Musculoskeletal disorders, Rapid Upper Limb Assessment RULA, Recommended Weight Limit RWL, Ergonomics.